KESIAPAN PEMERINTAH KOTA DUMAI DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Rendy Persada; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the prepared of Dumai City Government toward an ASEAN Economic Community in 2012-2015. ASEAN Economic Community are create by ASEAN Member toward a China, India and Japan economic groeth. In order that ASEAN make a common market to integrated te market in ASEAN and it will be power to support the economic groth of ASEAN members.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the prepared of Dumai City Government toward an ASEAN Economic Community. The theories applied in this research are liberalism perspective with the globalization theory by Robert W Cox.The research shows that prepared of Dumai City Government toward an ASEAN Economic Community are in economic and infrastructure. Some of policies are Dumai Government increase of foregin invest in Dumai City. Create a some regulations in investment trade, increase a growth in infrastructure and Dumai Government implemented of Saving economic in subdistrict in Dumai City.Key words: Dumai, economic community, invest and trade.